Economia circular e desenvolvimento sustentável: estratégias empreendedoras para os catadores de materiais reutilizáveis no território de bom futuro Barcarena-Pa - SILVA, Andréa Cristina dos Santos e (Universidade Federal do Pará, 2025)
The dissertation emphasizes the circular economy as a sustainable economic model, providing an instrument for entrepreneurship practices in the territory of Bom Futuro, located in the municipality of Barcarena–PA, where there are specific geopolitical configurations of a free landfill associated with housing disorder in the community, under a space with deficient conditions regarding fundamental basic assistance. The objective of this research is to insert environmental agents into the local scenario, to apply strategies to achieve the objectives of the three sustainable axes (3 RS) and generate income from waste. In general, promote the reuse and recycling economy; the Federal Republic of Germany is included as a notable citation in the selective collection chain; and, finally, analyze the collectors of reusable materials in your area of activity. The methodological approach to research may vary according to the nature of the research, quantitative approach, based on sources of information and sample collection; qualitative approach, through participatory interviews in organized groups, following territorial dynamics; exploratory, descriptive and explanatory typology. Recyclable collection agents present social and economic characteristics of vulnerability, precarious work, exposed to risks, unhealthy conditions and environmental damage, in addition to low financial income. In view of what was presented, an educational product, a practical manual on sustainable enterprises in accessible language, aims to raise awareness of alternative innovations, reestablishing the informal market. In this way, it is intended to shed light on proposals that reposition regional creative sectors, establishing endogenous development through actions that encourage the fight against segregation and poverty.